Exploring the role of normative, financial and environmental information in promoting uptake of energy efficient technologies. (June 2019) - Hafner, By Rebecca; Elmes, David; Read, Daniel; White, Mathew P.
Abstract: The potential of normative and feedback (financial vs. environmental) information in guiding pro-environmental decision-making behaviour was explored in a 2 × 2 (plus control) choice experiment. Using the context of home heating, 599 non-student participants from the UK general public were asked to choose between a standard heating system (a gas boiler) and a relatively more-energy efficient option (a heat pump). In line with evidence for the energy efficiency gap for sustainable innovations, there was low uptake of the heat pump (32.5%) in the control condition where no frame information was provided. Yet, in both conditions where normative information was provided, respondents were significantly more likely (vs. control) to choose the heat pump (financial + norm OR 3.63; 95% CIs 2.13, 6.19; environmental + norm OR 3.09; 95% CIs 1.67, 4.79), advancing understanding of normative social influence in the context of pro-environmental purchase behaviour. When normative information was not provided, only financial (OR 2.82; 95% CIs 1.67, 4.79) but not environmental (OR 1.33; 95% CIs 0.78, 2.26), feedback was associated with a significantly greater likelihood of heat pump choice. The main effect of normative information was replicated for behavioural intentions (though only for homeowners), but there was no norm-feedback interaction (regardless of homeownership). The implications for researchers looking to promote 'green' choice in the context of new technology adoption are discussed. Highlights: Empirical exploration of alternate decision frames in promoting 'green' choice. Focus on context of energy-efficient versus standard technology adoption in homes. Normative info increased likelihood of 'choosing green'; overruling feedback type. Financial feedback most effective in changing behaviour when no norm info is given. Implications for behaviour change efforts in this context are discussed.